The Influence of Electronic Teaching Materials on Students' Mastery of Learning Mathematics and Science: Meta-Analysis - Yelfi Rahmi; Asrizal Asrizal; Hilma Fadhilah; Iskandar Zulkarnain (Postgraduate, University of Mataram, 2023)
The use of teaching materials has an important effect on achieving learning objectives. Teaching materials for learning must be appropriate and as needed. The purpose of this study was to determine the effect of electronic teaching material models on MIPA students' mastery of learning. This type of research is meta analysis. Meta analysis is research conducted by summarizing, reviewing, and analyzing data from several studies that have been conducted. The research sample consisted of 30 nationally accredited journals with criteria according to the problem formulation. The data analysis technique used in this study is to calculate the effect size of each article. Based on the research results, it is known that the effect of electronic teaching materials on MIPA learning mastery with an average effect size of 1.97 and an average effect size of 0.09